Transformasi Pembelajaran Pendidikan Agama Islam di Era Digital: Tantangan, Peluang, dan Strategi Implementasi - Shoimul ‘Arofah As-Syadzili; Sheif Agil Choir; Rahmad Krize; Nur Khoirul Mubin (Civiliza Publishing, Indonesia., 2026)
The rapid advancement of digital technology, driven by the Industrial Revolution 4.0, Society 5.0, and the development of Artificial Intelligence (AI), has transformed educational practices, including Islamic Religious Education (Pendidikan Agama Islam/PAI). This transformation requires innovative learning approaches that integrate digital technology while maintaining Islamic values and character development. This study aims to analyze the transformation of PAI learning in the digital era by identifying its challenges, opportunities, and implementation strategies. The research employed a qualitative library research approach using relevant scientific literature, including journal articles, books, and policy documents published between 2021 and 2026. Data were analyzed through content analysis involving data reduction, categorization, interpretation, and synthesis. The findings indicate that digital transformation enhances learning through AI, Learning Management Systems, blended learning, and adaptive learning. However, significant challenges remain, including limited digital competence among teachers, ethical concerns regarding AI, information overload, cyber risks, and declining critical thinking skills among students. Therefore, successful implementation requires strengthening digital pedagogy, AI literacy, curriculum innovation, institutional support, and the integration of Islamic values into technology-based learning. This study concludes that digital transformation in PAI should prioritize technological innovation while preserving the moral, spiritual, and educational objectives of Islamic education to create adaptive, ethical, and meaningful learning experiences.